2017
DOI: 10.4292/wjgpt.v8.i1.39
|View full text |Cite
|
Sign up to set email alerts
|

Update on clinical and research application of fecal biomarkers for gastrointestinal diseases

Abstract: Gastrointestinal (GI) diseases comprise a large spectrum of clinical conditions ranging from indigestion to inflammatory bowel diseases (IBDs) and carcinomas. Endoscopy is the usual method employed to diagnose these condition. Another noninvasive way to assess and diagnose GI conditions are fecal biomarkers. Fecal biomarkers provide information regarding a specific disease process and are perhaps more acceptable to clinicians and patients alike because of their non-invasivity compared to endoscopy. Aim of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
47
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 47 publications
4
47
0
4
Order By: Relevance
“…Multiple investigators have explored the range of FCP levels which most accurately reflects mucosal inflammation that range from 50 to 250 ug/mL [7][8][9][10][11][12]. While several prior studies have used FCP levels below 250 ug/mL [7][8][9][10][11], we confirmed that the FCP cutoff value of 250 ug/mL significantly correlated with the presence of active disease and severity of inflammation confirmed by both MRE and colonoscopy, respectively. This FCP cutoff value, which is in line with the Colombel et al…”
Section: Correlation Between Cdeis and Mariasupporting
confidence: 69%
See 2 more Smart Citations
“…Multiple investigators have explored the range of FCP levels which most accurately reflects mucosal inflammation that range from 50 to 250 ug/mL [7][8][9][10][11][12]. While several prior studies have used FCP levels below 250 ug/mL [7][8][9][10][11], we confirmed that the FCP cutoff value of 250 ug/mL significantly correlated with the presence of active disease and severity of inflammation confirmed by both MRE and colonoscopy, respectively. This FCP cutoff value, which is in line with the Colombel et al…”
Section: Correlation Between Cdeis and Mariasupporting
confidence: 69%
“…The biomarker, FCP, is a heat stable granulocyte-derived protein that is released by activated neutrophils of the intestinal immune system in response to inflammation and then absorbed into feces [2]. Numerous studies have shown that FCP levels correlate well with intestinal inflammation with high levels of sensitivity and specificity [7][8][9][10][11][12]. Colombel et al, in one of the largest trials of tight control management of patients' with CD, established a FCP level of 250 mg/g or greater as abnormally elevated [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maturity of gastrointestinal function and inflammation can be assessed using faecal biomarkers, which provide a non-invasive and early method for detecting any increased risk for these conditions. 9 Alpha-1 antitrypsin is a serum trypsin inhibitor that is highly resistant to intestinal proteolysis. The extravasation of alpha-1 antitrypsin into the gut can be measured in the stools and is a classic marker for protein-losing enteropathies or conditions that result in loss of blood proteins into the intestinal tract.…”
Section: Introductionmentioning
confidence: 99%
“…Calprotectin belongs to a family of calcium‐binding proteins which are expressed in phagocytes, monocytes, macrophages and granulocytes . These proteins are released in the gastrointestinal tract during intestinal inflammation and can easily be measured in the faeces.…”
Section: Introductionmentioning
confidence: 99%